Utilization of Fly Ash and Polypropylene Wastes in the Production of a New Porous Composite Material - Yildirim, M. Sukru; Bicer, Yasar; Yildiz, Cengiz (Springer, 1996)
This work was undertaken on two different wastes to produce a new construction material which may have good insulation and mechanical strength properties. Fly ash, a waste produced at power stations, and polypropylene, a waste generated mostly from packaging, were used to produce smooth-surfaced test blocks. Compressive and tensile strength, abrasion, water absorption, thermal conductivity and specific heat capacity tests were done on these blocks. It was concluded that these two wastes could be utilized to produce useful insulation and other building materials and at the same time eliminate environmental problems that may be caused by them if disposed off.
Keywords: fly ash; poly propylene; insulation; composite material